EFEKTIVITAS BADAN USAHA MILIK DESA (BUMDes) DALAM MENDUKUNG LITERASI DIGITAL PRODUK USAHA MASYARAKAT DI DESA KERTAHARJA KECAMATAN CIJEUNGJING KABUPATEN CIAMIS - Aceng Nursobah; Arie Budiawan; Neti Sunarti (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This research is motivated by the low digital literacy of MSMEs in Kertaharja Village, Cijeungjing District, in the digital era that demands the ability to utilize information technology in marketing and business development. Although digital technology opens up wider market opportunities, most village MSMEs still run their businesses conventionally due to limited access, lack of training, and minimal understanding of the use of online platforms. Of the 152 existing MSMEs, only 25% have utilized digital media. BUMDes as a village economic institution has a strategic role in supporting the digitalization of community businesses, but the digital literacy program implemented is still not optimal. This condition encourages the need for research to analyze the effectiveness of BUMDes in supporting digital literacy of community business products and identifying obstacles and opportunities for digital-based village economic development. This study aims to determine the effectiveness of Village-Owned Enterprises (BUMDes) in supporting digital literacy of community business products in Kertaharja Village, Cijeungjing District, Ciamis Regency. The research method used was a qualitative descriptive method through observation, interviews, and documentation techniques, with six informants consisting of village officials, BUMDes administrators, and business actors who use and do not use digital technology. Data analysis techniques included data reduction, data presentation, and drawing conclusions. The results showed that the effectiveness of BUMDes in supporting digital literacy has not been optimal in five dimensions. In the dimension of goal achievement, the number of training participants and the level of digital skills improvement are still low. From the aspect of operational efficiency, the utilization of digital facilities is not optimal. In the dimension of program relevance, training materials do not fully match the needs of MSMEs. Stakeholder satisfaction is also not high due to the lack of follow up mentoring. As for the dimension of program sustainability, BUMDes still faces budget and human resource limitations. Overall, BUMDes has made efforts to support community digital literacy, but its effectiveness still needs to be improved through ongoing training, strengthening facilities, and programs that are more relevant to the needs of business actors.